(3cJGH GdOQ GdfXje aj Qhe GdJYde hGdJYdjes - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa ef hab HGdYde hGdYed hHYO agPg QSGdI eTJedI Ydi HjGf TQhW JYdje GdYdhe hJYdegG s
(3BNQgG (B:s
(3hEf cGf OGNdkG ai GdYde GdJYdjei bO CaQO YdekG Ydi MOJg hGdMeO ddg hMOg hUdi Gddg Ydi ef dGfHi HYOg bO JeJ gPg GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjSH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3HChdg aGFOIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs